Ketimpangan Ekonomi dan Dampaknya terhadap Perilaku Konsumen: Wawasan dari Komunitas Muslim Banjar - Muhammad Hikam; Siswanto; Ahmad Djalaluddin (Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman, 2024)
Economic inequality significantly influences consumer behavior, especially within culturally unique communities like the Muslim Banjar community in South Kalimantan, Indonesia. This study aims to explore the psychological and cultural impacts of economic inequality on consumer preferences, particularly toward advertising appeals emphasizing personal control. Using experimental methods involving 653 participants across five studies, the research reveals that higher economic inequality evokes financial threat perceptions, reduces a sense of control, and increases preferences for empowerment-focused advertisements. The findings further indicate that cultural values, such as family solidarity and religious beliefs, moderate these effects, mitigating the adverse impacts of inequality. The implications suggest a dual approach in advertising strategies—emphasizing both personal and collective empowerment—to address consumer needs in economically unequal societies. These insights provide valuable guidance for marketers and policymakers in crafting culturally sensitive and effective interventions.